2005
DOI: 10.1179/174327805x66245
|View full text |Cite
|
Sign up to set email alerts
|

Failure mechanisms and material degradation processes at high temperatures in ammonia synthesis

Abstract: Ammonia has been manufactured on an industrial scale for almost 100 years. Nevertheless, this process still presents a challenge to the materials involved and to the material engineers who are responsible for the selection of materials. This is due to the temperatures and the media handled. Failure mechanisms that have been known in ammonia plants since the industrial production of ammonia started are hydrogen attack, creep and embrittlement. Since the new generation of plants characterised by optimised heat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Magnetron sputtering was selected to produce such films because in addition to its versatility, it has the potential to be adapted for the coating of tubes, 13 components commonly involved in metal dusting failures. [1][2][3][4] Based on the areas for improvement detected in, 12 the present investigation further explores the d.c. RMS process parameters that can lead to such improvements for Al oxide coatings on 304L stainless steel, a material often used in environments where metal dusting occurs. 14,15 Experimental procedure…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetron sputtering was selected to produce such films because in addition to its versatility, it has the potential to be adapted for the coating of tubes, 13 components commonly involved in metal dusting failures. [1][2][3][4] Based on the areas for improvement detected in, 12 the present investigation further explores the d.c. RMS process parameters that can lead to such improvements for Al oxide coatings on 304L stainless steel, a material often used in environments where metal dusting occurs. 14,15 Experimental procedure…”
Section: Introductionmentioning
confidence: 99%
“…A number of processes in the chemical, petrochemical, materials transformation, energy, nuclear, and other industries are affected by metal dusting. Examples include hydrogen production, 1 ammonia synthesis, 2 ethylene cracking, 3 processing of mineral oil, 4 among several more.…”
Section: Introductionmentioning
confidence: 99%
“…Metal dusting is a high temperature corrosion mechanism relevant to iron, nickel, or cobalt alloys which are exposed to carbon producing atmospheres (i.e., mixtures of carbon monoxide, hydrogen, water vapor, and carbon dioxide) typically between 500 and 750 °C. It is observed for equipment used in hydrogen, ammonia, methanol, and gas‐to‐liquids production plants . Carbon monoxide from the gas atmosphere reacts at the metallic surface to form atomic carbon, which diffuses into the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The metallic substrate supersaturates in carbon and therefore decomposes into a mixture of graphite, oxidic, carbidic, and metallic particles (“metal dust”) . This leads to the formation of pits and possibly loss of containment …”
Section: Introductionmentioning
confidence: 99%
“…Several reviews of industrial failures due to metal dusting have been reported in literature 13–16. These have mainly covered wrought alloys.…”
Section: Introductionmentioning
confidence: 99%